Determination of Indonesia’s Exports to ASEAN-4 - Soeharjoto, Soeharjoto; Tribudhi, Debbie Aryani; Soeharjoto, Isamu Rafael (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
In globalization era, every country has the opportunity to increase its exports. Indonesia as one of the ASEAN member countries, participates in the ASEAN Economic Community. In winning the competition in the AEC market, Indonesia implements a strategy of prioritizing its exports to large importing countries of products from Indonesia. Singapore, Malaysia, Thailand, and Philippines are the four largest export destinations of Indonesia in the ASEAN member. However, the government also needs to pay attention to several macroeconomic indicators of the country, such as Gross Domestic Product per capita, exchange rates, and interest rates that can affect the demand for Indonesia's export destinations in ASEAN member countries. Aims of this study is to determine the determination of Indonesia's exports to ASEAN-4. The study used panel data in 2012-2021 from ASEAN-4, which came from Singapore, Malaysia, Thailand, and Philippines. This study was conducted using panel data regression method, using exports as the dependent variable and Gross Domestic Product per capita, exchange rate, and interest rate as dependent variable. The appropriate method used in this study is common effect model. This research obtained the results that Gross Domestic Product per capita and exchange rates have a positive and significant effect on Indonesia's exports to ASEAN-4. However, interest rates have no effect on Indonesia's exports to ASEAN-4.